Facile preparation of anisotropic PLA/CNT nanocomposites by hot and cold rolling processes for improving mechanical and conductive properties. Issue 33 (13th July 2022) - Huang, An; Song, Xincheng; Liu, Fan; Wang, Haokun; Geng, Lihong; Chen, Binyi; Peng, Xiangfang; Wang, Zhen; Tian, Genlin
Abstract: Poly(lactic acid) (PLA) is one of the most important biodegradable polymers, however, brittleness severely limits its applications. Thus, strengthening and toughening PLA is a cutting‐edge research for both academia and industry. In this study, rolling process was applied to simultaneously improve the toughness and strength of PLA and its nanocomposites by regulating microstructure of PLA molecular chains. Results showed that crystallinity and orientation of rolled PLA and its nanocomposites were significantly improved. When rolling rate was 50% at 75°C, elongation at break increased from unrolled PLA of 5.9% to 190.1%. When the rolling rate was 50% at room temperature, tensile strength and Young's modulus increased from unrolled PLA of 59.4 and 1763.7 MPa to 70.4 and 2557.6 MPa, respectively. In addition, multiwalled carbon nanotubes (MWCNTs) in PLA/3 wt.%CNT nanocomposite rolled at 75°C for 50% were highly oriented, leading to a significant reduction in resistivity along the rolling direction, which endows it many great potential applications, such as sensor, electromagnetic wave absorption, and electronic packaging. Abstract : Rolling process leads to anisotropy in PLA and PLA/CNT nanocomposites